2014
DOI: 10.1021/jf503620r
|View full text |Cite
|
Sign up to set email alerts
|

Decoupling Macronutrient Interactions during Heating of Model Infant Milk Formulas

Abstract: Understanding macronutrient interactions during heating is important for controlling viscosity during infant milk formula (IMF) manufacture. Thermal behavior of macronutrients (casein, whey, lactose, fat) was studied, in isolation and combination, over a range of concentrations. Addition of phosphocasein to whey protein solutions elevated denaturation temperature (Td) of β-lactoglobulin and the temperature at which viscosity started to increase upon heating (Tv). Secondary structural changes in whey proteins o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 49 publications
(93 reference statements)
2
22
0
4
Order By: Relevance
“…For pre-heated solutions, a decrease in denaturation temperature occurred, although the decrease occurred at a lower denaturation temperature and was not statistically significant. It has previously been observed that increasing the protein concentration of β-LG results in a decrease in its denaturation temperature (Qi et al, 1995), with comparable results also observed in mixed whey protein systems (Boyle and Alli, 2000;Murphy et al, 2014).…”
Section: Protein Denaturationsupporting
confidence: 73%
“…For pre-heated solutions, a decrease in denaturation temperature occurred, although the decrease occurred at a lower denaturation temperature and was not statistically significant. It has previously been observed that increasing the protein concentration of β-LG results in a decrease in its denaturation temperature (Qi et al, 1995), with comparable results also observed in mixed whey protein systems (Boyle and Alli, 2000;Murphy et al, 2014).…”
Section: Protein Denaturationsupporting
confidence: 73%
“…The presence of increased levels of lactose, which can provide some thermal protection to whey proteins (Murphy et al . ), in UF manufactured WPI was offset, in this case, by the dissimilar mineral composition (mono‐ and di‐valents) compared to ion‐exchange manufactured WPI.…”
Section: Resultsmentioning
confidence: 96%
“…In addition, surge in loading around 1620-1618 cm -1 had also been attributed to disruption of intramolecular hydrogen bonds within a secondary structure, leading to formation of new stronger intermolecular hydrogen bonds (Ngarize, et al, 2004). However, unlike previously reported (Murphy, Fenelon, Roos, & Hogan, 2014), increase in intermolecular β sheet (1686 and 1618 cm -1 ) in the current study was not followed with concomitant decline in α-helix (1653 cm -1 ) and intramolecular β sheet structure (1630−1627 cm -1 ). It appeared that though there was an enhancement in intermolecular interactions leading to the aggregation, it was not at expense of intramolecular interactions.…”
Section: Region III Protein (Amide I and Amide Ii) 1700-1500 Cm -1mentioning
confidence: 92%